Model of adaptive behavior of enterprises in the context of transformational changes associated with the aggravation of the climate crisis - A.M. Tkachenko; O.V. Hryhorieva (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
It is stated that in the current conditions of the activity of enterprises, the external environment acts as a catalyst for adaptive organizational changes, which in recent years has been increasingly acquiring cardinal transformations, thereby predetermining the VUCA conditions for the functioning of business entities, which requires the mandatory formation of an adaptation policy by them, as an integral part of the management system. and fundamental basis for further development. It is noted that ensuring the effectiveness of the adaptation policy, as practice shows, is possible only with the right choice of strategy and model of adaptive behavior of enterprises aimed at achieving certain guidelines for their development. It has been substantiated that the specificity of the modern conditions of managing enterprises determines the expediency of an organic synthesis of the theory of adaptation with the theory of strategic management. It is emphasized that the adaptation of the existing potential to the requirements and needs of the future involves the formation of an adaptation strategy by enterprises, which, in the conditions of accelerated transformations, in particular, as a result of the exacerbation of the climate crisis, should be determined according to the scenario approach, which will allow building a portfolio of the external environment, and, consequently, a vision of the expected the prospects for its changes on short-term and long-term time horizons. The definitions of the interpretation of the concept of “adaptation” are considered and the approaches to their formation are analyzed. It has been proved that the strategic management of enterprises, adapted to economic transformations due to climate change, should focus primarily not on solving existing problems, but on using the opportunities and strengths of the enterprise. It is emphasized that, depending on the role and importance of adaptive elements, as well as readiness for an adaptive response, it is customary to distinguish three models of behavior of enterprises, each of which determines the readiness for adaptation: a model of active, conservative and mixed behavior. Each of the models of adaptive behavior of enterprises is analyzed. The need for accelerated climate change and transformations in the economy to apply a mixed model of adaptive behavior of enterprises is substantiated.